Ontogenetic changes in stomatal and biochemical limitations to photosynthesis of two co-occurring Mediterranean oaks differing in leaf life span (Tree Physiology, 2008)
A quantitative analysis was applied to the stomatal and biochemical limitations to light-saturated net photosynthesis under optimal field conditions in mature trees and seedlings of the co-occurring evergreen oak, Quercus ilex L., and the deciduous oak, Q. faginea Lam. Stomatal limitation to photosynthesis, maximal Rubisco activity and electron transport rate were determined from assimilation versus intercellular leaf carbon dioxide concentration response curves of leaves that were subsequently analyzed for nitrogen (N) concentration, mass per unit area, thickness and percent internal air space. In both species, seedlings had a lower leaf mass per unit area, thickness and leaf N concentration than mature trees. The root system of seedlings during their third year after planting was dominated by a taproot. A lower leaf N concentration of seedlings was associated with lower maximal Rubisco activity and electron transport rate and with assimilation rates similar to or lower than those of mature trees, despite the higher stomatal conductances and potential photosynthetic nitrogen-use efficiencies of seedlings. Consequently, stomatal limitation to photosynthesis increased with tree age in both species. In both seedlings and mature trees, a lower assimilation rate in Q. ilex than in Q. faginea was associated with lower stomatal conductance, N allocation to photosynthetic functions, maximal Rubisco activity and electron transport rate, and potential photosynthetic nitrogen-use efficiency but greater leaf thickness and leaf mass per unit area. Tree-age-related changes differed quantitatively between species, and the characteristics of the two species were more similar in seedlings than in mature trees. Despite higher stomatal conductances, seedlings are more N limited than adult trees, which contributes to lower biochemical efficiency.
10.1093/treephys/28.3.367

Stomatal responses to drought of mature trees and seedlings of two co-occurring Mediterranean oaks - Mediavilla, Sonia; Escudero, Alfonso (Forest Ecology and Management, 2004)
We studied stomatal responses to decreasing predawn water potential (Cpd ) and increasing leaf-to-air water vapour pressure deﬁcit (VPD) of seedlings and mature trees of two co-occurring Mediterranean oaks with contrasting leaf habits: the evergreen Quercus rotundifolia and the deciduous Quercus faginea. Our objective was to deﬁne and to compare the stomatal strategies of both speciesfordroughtresistanceandtoidentifythepossibledifferencesbetweengrowthstagesinselecteddroughtadaptationattributes. Among the mature trees, Q. rotundifolia exhibited a water-use behaviour that was more conservative than that of Q. faginea: lower maximum stomatal conductances and greater sensitivity to VPD than the deciduous species. As a result, the leaf water potential of the evergreen species never decreased along the day and along the growth season as much as in the deciduous species; this may help to guarantee longer leaf longevity by avoiding irreversible damage during the summer drought. The seedlings of the two species showed a less conservative water-use strategy in comparison with adult trees: a relatively high stomatal conductance and lower stomatal sensitivity to soil and atmospheric drought. As a consequence, leaf water potential decreased more in the seedlings along the day than in the adults. Q. rotundifolia was the species for which the most pronounced differences between growth stages were obtained. Thus, interspeciﬁc differences in response to drought disappeared in the ﬁrst stages of the life of the trees, and the seedlings of the two species showed a common strategy, probably as a response to the competition from the herbaceous layer. A low stomatal sensitivity in beneﬁt of an increase in growth would probably be a more successful strategy under the competitive conditions that seedlings experience during their establishment.
Keywords: Drought; growth stages; leaf water potential; mediterranean quercus species; Stomatal conductance; vapour pressure deficit

Stomatal responses to drought of mature trees and seedlings of two co-occurring Mediterranean oaks (Forest Ecology and Management, 2004)
We studied stomatal responses to decreasing predawn water potential (Cpd ) and increasing leaf-to-air water vapour pressure deﬁcit (VPD) of seedlings and mature trees of two co-occurring Mediterranean oaks with contrasting leaf habits: the evergreen Quercus rotundifolia and the deciduous Quercus faginea. Our objective was to deﬁne and to compare the stomatal strategies of both speciesfordroughtresistanceandtoidentifythepossibledifferencesbetweengrowthstagesinselecteddroughtadaptationattributes. Among the mature trees, Q. rotundifolia exhibited a water-use behaviour that was more conservative than that of Q. faginea: lower maximum stomatal conductances and greater sensitivity to VPD than the deciduous species. As a result, the leaf water potential of the evergreen species never decreased along the day and along the growth season as much as in the deciduous species; this may help to guarantee longer leaf longevity by avoiding irreversible damage during the summer drought. The seedlings of the two species showed a less conservative water-use strategy in comparison with adult trees: a relatively high stomatal conductance and lower stomatal sensitivity to soil and atmospheric drought. As a consequence, leaf water potential decreased more in the seedlings along the day than in the adults. Q. rotundifolia was the species for which the most pronounced differences between growth stages were obtained. Thus, interspeciﬁc differences in response to drought disappeared in the ﬁrst stages of the life of the trees, and the seedlings of the two species showed a common strategy, probably as a response to the competition from the herbaceous layer. A low stomatal sensitivity in beneﬁt of an increase in growth would probably be a more successful strategy under the competitive conditions that seedlings experience during their establishment.